STRATEGI PENGEMBANGAN USAHA OUTER SCARF “DESIRE & CO” CIMAHI - Dita Amanah; Nida Azka Pauziyyah; Dedy Ansari Harahap (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2023)
This study was conducted on an online business in Cimahi called Desire & Co, which sells outer scarves with various motifs that can be selected or ordered according to the desired motif. Observation results show that there are several problems faced by this business, namely promotion on social media that is less consistent, lack of capital to advertise, poor quality product photos, and lack of human resources. This business is still implementing the red ocean strategy because it is relatively new and has many competitors. Observation of the running of the business is done by making a questionnaire and asking the owners and employees and used as a method of collecting data for this research. The solution that has been given is to use the hookle application so that promotions are consistent, optimize product photos on social media as an advertising platform and expand advertisements to various other social media.